2006
DOI: 10.1016/j.cognition.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of prosody in the interpretation of structural ambiguities: A study of anticipatory eye movements

Abstract: An eye-tracking experiment examined whether prosodic cues can affect the interpretation of grammatical functions in the absence of clear morphological information. German listeners were presented with scenes depicting three potential referents while hearing temporarily ambiguous SVO and OVS sentences. While case marking on the first noun phrase (NP) was ambiguous, clear case marking on the second NP disambiguated sentences towards SVO or OVS. Listeners interpreted caseambiguous NP1s more often as Subject, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 14 publications
3
91
2
Order By: Relevance
“…The visual world paradigm has further revealed the rapid influence of prosodic information in disambiguating word-order ambiguity (Weber, Grice, & Crocker, 2006) as well as of stress for identifying contrasting referents (Weber, Braun, & Crocker, 2006). Perhaps most important with regard to the present proposal is the evidence regarding the on-line influence of non-linguistic information, such as visual referential context (Tanenhaus et al, 1995), object affordances (Chambers, Tanenhaus, & Magnuson, 2004), depicted events (Knoeferle et al, 2005), and motor resonance (Zwaan & Taylor, 2006).…”
Section: Sentence Interpretationmentioning
confidence: 86%
See 1 more Smart Citation
“…The visual world paradigm has further revealed the rapid influence of prosodic information in disambiguating word-order ambiguity (Weber, Grice, & Crocker, 2006) as well as of stress for identifying contrasting referents (Weber, Braun, & Crocker, 2006). Perhaps most important with regard to the present proposal is the evidence regarding the on-line influence of non-linguistic information, such as visual referential context (Tanenhaus et al, 1995), object affordances (Chambers, Tanenhaus, & Magnuson, 2004), depicted events (Knoeferle et al, 2005), and motor resonance (Zwaan & Taylor, 2006).…”
Section: Sentence Interpretationmentioning
confidence: 86%
“…While inspecting a scene that showed, for example, a boy, a toy train and car, a ball, and a birthday cake, people's inspection of the cake was increased when they heard The boy will eat ... versus The boy will move ..., indicating that people rapidly use verb semantics to anticipate likely patients of the verb. Such anticipatory looks are also sensitive to linguistic (Kamide et al, 2003) and prosodic (Weber, Grice, & Crocker, 2006) constraints on grammatical function and thematic roles imposed by compositional interpretation. Knoeferle et al (2005) also found evidence for the anticipation of role fillers based on participants in verb-mediated depicted scene events.…”
Section: Utterance-mediated Attentionmentioning
confidence: 99%
“…Or it may be that the effects of prosodic boundaries are generally delayed. In fact, there is little evidence about when prosodic boundary effects occur during on-line comprehension (see Kjelgaard & Speer, 1999, for suggestive evidence of their on-line nature; see also Dahan, Tanenhaus, &Chambers, 2002, andWeber, Grice, &Crocker, 2006, for on-line evidence that pitch accent placement can affect information structure and sentence interpretation).…”
Section: Discussionmentioning
confidence: 99%
“…These effects of prosody emerge quickly during online sentence comprehension, suggesting that this is a robust property of the human parser (Marslen-Wilson, Tyler, Warren, Grenier, & Lee, 1992;Nagel, Shapiro, Tuller, & Nawy, 1996;Pynte & Prieur, 1996;Kjelgaard & Speer, 1999;Steinhauer, Alter & Frederici, 1999;Snedeker & Trueswell, 2003;Warren, Grabe & Nolan, 1995;Weber, Grice & Crocker, 2006). Naïve speakers systematically vary their prosody depending on the syntactic structure of the utterance and naïve listeners can use this variation to disambiguate the utterance (Snedeker & Trueswell, 2003;Schafer, Speer & Warren, 2005;Kraljic & Brennan, 2005).…”
Section: Authors' Notementioning
confidence: 99%